2001
DOI: 10.1152/jappl.2001.90.6.2439
|View full text |Cite
|
Sign up to set email alerts
|

Effects of one-legged endurance training on femoral arterial and venous size in healthy humans

Abstract: The cross-sectional area (CSA) of large-conductance arteries increases in response to endurance training in humans. To determine whether training-induced changes in arterial structure are systemic in nature or, rather, are confined to the arteries supplying exercising muscles, we studied 10 young men who performed one-legged cycle training [80% of one-legged peak O2 uptake (VO2 peak)), 40 min/day, 4 days/wk] for 6 wk and detraining for another 6 wk. There were no significant differences in baseline one-legged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
89
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 103 publications
(97 citation statements)
references
References 28 publications
7
89
1
Order By: Relevance
“…Persistent changes in blood flow cause alterations in blood vessel architecture to normalize wall shear stress. 3,5 Previous training studies 29,30 in humans have suggested that conduit arteries adapt their base- line diameters to peak shear stress and peak oxygen consumption rather than to resting blood flow. Parallel to this reasoning, the decrease in diameter in SCI may represent an inward remodeling as an adaptation to a total lack of periods of high shear stress in the paralyzed legs of people with SCI.…”
Section: Baseline and Hyperemic Vascular Characteristicsmentioning
confidence: 99%
“…Persistent changes in blood flow cause alterations in blood vessel architecture to normalize wall shear stress. 3,5 Previous training studies 29,30 in humans have suggested that conduit arteries adapt their base- line diameters to peak shear stress and peak oxygen consumption rather than to resting blood flow. Parallel to this reasoning, the decrease in diameter in SCI may represent an inward remodeling as an adaptation to a total lack of periods of high shear stress in the paralyzed legs of people with SCI.…”
Section: Baseline and Hyperemic Vascular Characteristicsmentioning
confidence: 99%
“…The findings of this study suggest that decreased compliance of peripheral small arteries may partly reduce peripheral blood flow, resulting in reduction in muscle volume in middle-aged and elderly individuals. On the other hand, recent studies have shown that moderate or high-intensity physical training induced an increase in the diameter of the femoral artery [29][30][31] , whereas femoral arterial compliance did not change in contrast with carotid arterial compliance 32) . Also, a previous study indicated that resistance training increased blood flow and vascular conductance of the femoral artery in middle-aged and elderly adults 33) .…”
Section: Discussionmentioning
confidence: 86%
“…This difference in diameter response suggests that the venous and arterial vascular systems are susceptible to different stimuli, when exposed to deconditioning. As arterial adaptations were ascribed to mainly regional factors due to (the lack of) physical exercise, such as changes in blood flow and (peak) shear stress to the vessel wall (Bleeker et al 2005b;Miyachi et al 2001), veins might be primarily responsive to changes in pressure or blood volume (Arbeille et al 2001). …”
Section: Discussionmentioning
confidence: 99%